The spatial and temporal dynamics of rabies in China - Tang, Q; Yu, J; Hao, L; Rayner, S; Liang, G (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Recent years have seen a rapid increase in the number of rabies cases in China and an expansion in the geographic distribution of the virus. In spite of the seriousness of the outbreak and increasing number of fatalities, little is known about the phylogeography of the disease in China. In this study, we report an analysis of a set of Nucleocapsid sequences consisting of samples collected through the trial Chinese National Surveillance System as well as publicly available sequences. This sequence set represents the most comprehensive dataset from China to date, comprising 210 sequences (including 57 new samples) from 15 provinces and covering all epidemic regions. Using this dataset we investigated genetic diversity, patterns of distribution, and evolutionary history.